Research on viral agents associated with feline reproductive problems reveals a high association with feline panleukopenia virus - Oliveira, Ilanna Vanessa Pristo de Medeiros; Freire, Débora Alves de Carvalho; Ferreira, Heider Irinaldo Pereira; Moura, Gabriela Hemylin Ferreira; da Rocha, Célio Souza; Calabuig, Cecilia Irene Pérez; Kurissio, Jacqueline Kazue [UNESP]; Junior, João Pessoa Araújo [UNESP]; Antunes, João Marcelo Azevedo de Paula (Elsevier, 2018)
Although reproductive failures (RF) such as abortion, stillbirth and neonatal mortality in cats are still under researched, it is known that many RF are caused by viral agents. This research surveyed the viral agent prevalence in queens with RF. Queens were excluded from the study if their RF was caused by issues other than infection, such as genetic, traumatic, hormonal or nutritional problems, or if they had a history of RF. Blood samples from 26 pregnant females with RF were collected for complete blood counts (BCC), renal/hepatic biochemistry and glycaemic analysis. Ultrasonography was performed to evaluate gestational age and foetal viability. When possible, placentas, humours and foetal tissues were collected. Blood samples were tested by PCR and qPCR for feline leukaemia virus (FeLV), feline immunodeficiency virus (FIV), feline alphaherpesvirus 1 (FeHV-1) and carnivore protoparvovirus 1 (CPPV-1). All maternal samples were negative for FeLV, FIV and FeHV-1 and positive for CPPV-1. In addition, foetuses from one queen and three females were positive for CPPV-1 by qPCR and for feline panleukopenia virus (FPV) through DNA sequencing. The BCC and biochemistry results revealed significant neutrophilia, lymphopenia, monocytosis, and liver enzymes. These results provide the first description of an FPV agent causing only RF-related clinical signs in queens.
Keywords: Felis catus; Infectious causes; Loss of pregnancy; Reproductive failures